Exploration of occupational injuries in food industry of Ukraine - Evtushenko, Olga; Klepikov, Igor (My University, 2013)
The aim of this work is carrying out of statistical analysis of occupational injuries among Food Industry employees. The object of research is occupational injury in Food Industry for 2003-2011 period. Status of occupational injury in Ukraine was analyzed for 2003-2011 period. We show a results of occupational injury dynamic research in Food Industry of Ukraine from 2003 to 2011 years. Distribution for male and female injured employees on enterprises of Food Industry was performed. Indexes of injury rate and heaviness were calculated. And finally, distribution of accidents for main reasons, sorts of events, profession group, age, work experience was performed.
Keywords: production traumatism; accident; виробничий травматизм; нещасний випадок; травматизм; кафедра екології та екоменеджменту